(untitled) (Педагогіка вищої та середньої школи, 2009)
Some models of preparation of teachers of initial classes in which optimum integrate personality and professional qualities are considered; specified on the necessity of change of strategic aims of pedagogical education, transpositions of accent from knowledges of specialist to his personality qualities which appear at the same time and as a purpose, and as a mean of his preparation to future professional activity.